Water paper paint : a creative card-painting kit - Smith Jones, Heather (Quarry Books, 2013)
This inspiring, everything-in-one card-painting kit blends traditional watercolor painting techniques with a fresh, contemporary sensibility. Learn unique techniques and design ideas for making beautiful, hand-painted greeting cards from the full-color 32 page book.